2018
DOI: 10.1080/16070658.2018.1503810
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, perceptions and practices of HIV-infected mothers regarding HIV and infant feeding

Abstract: The objective of this study was to determine the knowledge, perceptions and practices of HIV-infected mothers regarding human immunodeficiency virus (HIV) and infant feeding. Design: A cross-sectional study design was applied. Setting: The study was undertaken at a regional hospital in Bloemfontein. Subjects: A total of 100 mother-infant pairs that were still in hospital after the delivery of the baby were included. All mothers were HIV-infected. Outcome measures: Sociodemographic information, medical history,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
6

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 19 publications
0
6
0
6
Order By: Relevance
“…Although women on the PMTCT programme attempt to breastfeed, exclusive breastfeeding seems insurmountable and difficult to sustain (Horwood et al 2019 ). A recent study has shown that lack of knowledge contributes to poor infant feeding practices by HIV-infected mothers (Robb, Walsh & Nel 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although women on the PMTCT programme attempt to breastfeed, exclusive breastfeeding seems insurmountable and difficult to sustain (Horwood et al 2019 ). A recent study has shown that lack of knowledge contributes to poor infant feeding practices by HIV-infected mothers (Robb, Walsh & Nel 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Conforme apresentado no Quadro 2, foram incluídos na revisão cinco artigos (Lemly et al, 2007;Lumbantoruan et al, 2020;Medina-Marino et al, 2020;Robb et al, 2018;Sarnquist et al, 2014), todos publicados em inglês, produzidos no período de 2007 a 2020. A maioria dos estudos foi produzida na África do Sul (60%), sendo um deles em parceria com os Estados Unidos (20%), um na França (20%) e um na Indonésia (20%).…”
Section: Resultsunclassified
“…In poor settings with limited resources, knowledge, perceptions, and practices of HIV-positive mothers concerning the feeding of their infants are inadequate (66,67). This implies that a sizeable percentage of infants are at increased risk of acquiring HIV through inappropriate feeding.…”
Section: Problems Affecting Feeding Practices Among Hiv-infected Infants and Childrenmentioning
confidence: 99%
“…Oral diseases are also common problems in HIV-positive children (75). Oral candidiasis is the most frequently found HIV-related oral manifestation which can affect infants' feeding practices (67,68). Dental diseases also affect HIVinfected children.…”
Section: Problems Affecting Feeding Practices Among Hiv-infected Infants and Childrenmentioning
confidence: 99%